2007
DOI: 10.1038/sj.cgt.7701073
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-specific dendritic cells generated by genetic redirection of Toll-like receptor signaling against the tumor-associated antigen, erbB2

Abstract: Dendritic cells (DC) perform an important role in the initiation of the immune response through the local secretion of inflammatory mediators within diseased tissue in response to Toll-like receptor (TLR) ligation. However, DC vaccine strategies fail to make use of this capability against cancer. To harness the TLR response capability of DC against cancer, we tested a series of recombinant genes for their ability to redirect DC function specifically against a tumor-associated antigen. Each gene encoded a cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…In addition, we will investigate the generality of this strategy through construction of other TAA-specific CR. Recently, Xu and colleagues (48) reported that a chimeric gene linking ErbB2-specific scFv to IRAK-1 signaling is able to mediate cytokine secretion and enhance T-cell stimulation capacity of DC cell line, which is consistent with our results. Perhaps integrating the components of TLR signaling into the CRs will reinforce the efficacy of targeted DC as reported recently by Lapteva and colleagues (49).…”
Section: Discussionsupporting
confidence: 82%
“…In addition, we will investigate the generality of this strategy through construction of other TAA-specific CR. Recently, Xu and colleagues (48) reported that a chimeric gene linking ErbB2-specific scFv to IRAK-1 signaling is able to mediate cytokine secretion and enhance T-cell stimulation capacity of DC cell line, which is consistent with our results. Perhaps integrating the components of TLR signaling into the CRs will reinforce the efficacy of targeted DC as reported recently by Lapteva and colleagues (49).…”
Section: Discussionsupporting
confidence: 82%
“…This cell line has been used for studies of antitumor (15,24,39) and pathogen-specific (23) immunity. In this study, we compared the characteristics of JAWS II cells to those of primary BMDCs and investigated their capacities to present Chlamydia antigens in vitro and in vivo in order to determine their potential for Chlamydia vaccine and antigen discovery studies.…”
mentioning
confidence: 99%
“…electroporation with mRNA encoding caTLR4, was recently shown to activate human DCs, resulting in priming of Melan-A CTL responses (Bonehill et al 2008). Using a similar cloning strategy Xu et al (Xu et al 2007) generated RVs encoding MyD88 or IRAK-1, two major adaptor molecules in TLR triggered activation pathways. Again they used the JAWSII DC line to evaluate the chimeric proteins, demonstrating that only the IRAK-1 chimera mediated IL-12 and TNF-α secretion, and enhanced OVA-specific CD4 + T cell responses.…”
Section: Engineering Lentiviral Vectors To Enhance the Immune Stimulamentioning
confidence: 99%
“…However, its clinical use is limited by its cytotoxicity. Therefore, the feasibility of using RVs encoding a constitutive active TLR4 (caTLR4) for DC maturation has been evaluated (Xu et al 2007). This was achieved by linking the cytoplasmic domain of TLR4 to the extracellular single-chain immunoglobulin anti-erbB2.…”
Section: Engineering Lentiviral Vectors To Enhance the Immune Stimulamentioning
confidence: 99%